DETERMINASI ROE DAN PERTUMBUHAN PERUSAHAAN TERHADAP IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY DIPASAR MODAL - Amali, Lanto Miriatin; Selvi, Selvi (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2026)
This research seeks to examine how Return on Equity (ROE) and Company Growth affect the adoption of Corporate Social Responsibility (CSR) practices among financial firms on the Indonesia Stock Exchange (IDX). Data from secondary sources, such as annual reports and financial statements from the years 2021 to 2024, were utilized. The dependent variable refers to the extent of CSR practices, whereas the independent variables consist of ROE representing financial health and company growth evaluated through variations in annual assets and income. The approach employed for analysis was multiple linear regression to assess the impact of ROE and Company Growth on CSR activities. The findings revealed that ROE does not influence CSR, suggesting management may not consider CSR investments as a direct way to enhance shareholder wealth. Additionally, Company Growth showed a negative but not significant impact. These outcomes indicate that as the growth of company assets rises, there is a corresponding tendency for CSR levels to decline, while ROE and company growth do play a role in influencing CSR activities. This implies that companies pursue CSR to earn legitimacy from their communities and stakeholders.